Pendampingan Pelatihan Pengisian SPT Pajak UMKM - Umar Yeni Suyanto; Rina Sulistyowati; Siti Nur Hayati (Biro Pengelolaan Penelitian dan Pengabdian Kepada Masyarat SETIA Ngabang, 2020)
This Community Service Activity (PKM) aims to provide training for MSME actors by providing an understanding of the requirements, calculations and procedures for reporting income tax, especially SPT. The partner problem that will be resolved in this activity is that some MSMEs in the Lamongan city area and its surroundings do not understand filling out SPT to report their tax obligations. The method applied to overcome this problem is to provide training through online seminars which are organized in collaboration with several lecturers from the Tax Study Program of the Ahmad Dahlan Business and Technology Institute. This activity was divided into 3 stages: planning, implementation and evaluation sessions. The results of the activity show an increase in understanding and knowledge after participating in training activities. This means that the objectives of this PKM have been achieved.